Perbedaan Defisit Neurologis Antara Stroke Iskemik Serangan Pertama Dan Serangan Berulang - Sulistiawaty, Puput Agus, Dr. Iwan Setiawan, Sp.S (2017)
Background: Stroke a disease that happened acute nerve function degradation which was because of venous trouble of brain, this was happened quickly.This especial symptom generate the neurological deficit symptom very sudden preceded with the symptom of prodromal and sign as according to annoyed brain blood. Purpose: To identify the difference of neurological deficit between first attack and repeated attacks ischemic stroke at patients in PKU Aisiyah Boyolali Hospital, Karangayar Area Public Hospitalat 2015-2016. Method: This research was using analytic observational with cross sectional method approach. Research sample was taken with purposive sampling technique so that obtained counted 32 patients sample consisted by 16 patients with first attack and 16 patients with repeated attack. This research was done during November 2016, first attack and repeated attacks ischemic stroke data was obtained from medic record note and neurological deficit measured was using National Institutes of Health Stroke Scale (NIHSS) questioner. Data was obtained to be analysed by using Mann Whitney test. Result: Based on analysis result was known that majority of ischemic stroke patients have woman gender (56,2%), have an age 56 - 65 years old (37,5%) with the mean of repeated attack stroke patients neurological deficit (11,813) more large than the mean of first attack stroke patients neurological deficit (7,063). Based on the Mann Whitney test analysis result was obtained significance value (p value) equal to 0,010 < 0,05. This matter can be interpreted that there was difference of neurological deficit between first attack and repeated attacks ischemic stroke. Kesimpulan: This matter can be interpreted that there was difference of neurological deficit between first attack and repeated attacks ischemic stroke at patients in PKU Aisiyah Boyolali Hospital, Karangayar Area Public Hospitalat 2015-2016.